Science level 1(the city school) (The City School, Albakio International Lahore, 2011)
Science Level 1 curriculum for The City School, designed for young learners to explore foundational scientific concepts. The curriculum emphasizes hands-on learning, critical thinking, and inquiry-based activities, fostering curiosity and a love for science. Key topics include the study of living organisms, the physical environment, and basic principles of physics and chemistry. Through interactive experiments, collaborative projects, and engaging resources, students develop essential skills in observation, investigation, and analysis. The program aims to inspire students to become inquisitive thinkers and problem solvers, laying a solid groundwork for their future academic endeavors in science.